Brazilian spotted fever: A reemergent zoonosis - Greca, H. [UNESP]; Langoni, Hélio [UNESP]; Souza, Luiz Carlos de [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
Brazilian spotted fever is caused by the bacterium Rickettsia rickettsii, which is the most pathogenic species of the spotted-fever rickettsiae group and is transmitted by the bite of infected ticks. Amblyomma cajennense is the most important tick species involved in the cycle of this zoonosis in Brazil as it presents low host specificity, great number of natural reservoirs and wide geographic distribution. It was first described in the state of São Paulo in 1929 and later in Rio de Janeiro, Minas Gerais and Bahia. The number of cases decreased in the 1940's with the development of new plague control techniques and antibiotics. In the last decades, the number of new cases has increased. The current review aimed at reporting some of the epidemiological and public health aspects of this reemergent disease with new foci, mainly in the southeastern region of Brazil.
Keywords: Brazilian spotted fever; rickettsia rickettsii; Amblyomma cajennense